An outer-approximation algorithm for maximum-entropy sampling - Fampa, Marcia; Lee, Jon (Discrete Applied Mathematics, 2024)
We apply the well-known outer-approximation algorithm (OA) of convex mixed-integer nonlinear optimization to the maximum-entropy sampling problem (MESP), using convex relaxations for MESP from the literature. We discuss possible methodologies to accelerate the convergence of OA, by combining the use of the different relaxations and by selecting additional linearization points using a local-search procedure, disjunctive cuts, a regularization method, and a second-order approximation of the objective of the MESP. We discuss our findings through numerical experiments with a benchmark test problem.